Paradigma Tradisionalisme, Modernisme dan Postmodernisme dalam Pendidikan Islam - Muhammad Thariq Aziz; Iin Khairunnisa; Mujib Abdullah Romdon; Ndaru Putri Yudiarti (Cendekia, 2023)
This research discusses the paradigms of traditionalism, modernism and postmodernism in Islamic education. The approach used in this research is qualitative with a library study type of research. Researchers try to dig up information and knowledge from various existing literature and references. Literature that serves as a reference about educational paradigms takes the form of books, notes, newspapers, research journals, and comments from educational figures. After all the data has been collected, the step to analyze the data is content analysis. by comparing and analyzing phenomena with theory, then the researcher analyzes the data and draws conclusions. The results of this study reveal that the paradigm developed to the postmodern paradigm as part of the critique of the modern paradigm. Postmodernism is a style of thinking that was born as a reaction to modernist thought which was considered to have many shortcomings and caused various human problems. The postmodern education paradigm refers to a curriculum that can change at the implementation level because the object of implementation, namely students also participate in it (decentralization). On the other hand, the postmodernism curriculum gives students a role as key players in the curriculum. Students can think critically, freely, and be creative with the knowledge they gain. However, this creative thinking process must also receive guidance from teachers who serve as facilitators or consultation media for students so that they do not get off track